Analysis of the in vitro cytotoxicity and genotoxicity of cellulose nanomaterials in intestinal cells - Vital, Nádia (2022)
Abstract publicado em: Environ Mol Mutagen. 2022 Aug;63(Suppl 1):88. (Abstracts from the 13th International Conference on Environmental Mutagens and 53rd Annual Meeting of the Environmental Mutagenesis and Genomics Society). https://onlinelibrary.wiley.com/toc/10982280/2022/63/S1